LEARNING FROM ATTITUDES - Soares, Domingos S. L. (Revista Latino-Americana de Educação em Astronomia, 2004)
From 1985 to 1989, I worked at the Kapteyn Laboratory - which is part of the Astronomy Faculty of the University of Groningen, The Netherlands - on my doctoral thesis project. During the whole period Prof. Hugo van Woerden was the Chairman of the Laboratory. From my recollections of that time I tell here three episodes in which Prof. van Woerden's attitudes are put in focus.